Risk, failure, play what dance reveals about martial arts training - O'Shea, Janet 1968- (Oxford University Press, 2019)
Risk, Failure, Play illuminates the many ways in which competitive martial arts writer differentiate themselves from violence. Presented from the perspective of a dancer and writer, this book takes readers through the politics of everyday life as experienced through training in a range of martial arts practices such as jeet kune do, Brazilian jiu jitsu, kickboxing, Filipino martial arts, and empowerment self-defense. author Janet O'Shea shows how play gives us the ability to manage difficult realities with intelligence and demonstrates that physical play, with its immediacy and heightened risk, is particularly effective at accomplishing task. Risk, Failure, Play intertwines personal experience with phenomenology, social psychology, dance studies, performance studies, as well as theories of play and competition in order to produce insights on pleasure, mastery, vulnerability, pain, agency, individual identity, and society. Ultimately, this book suggests that play allows us to rehearse other ways to live that the ones we see before us and challenges us to reimagine our social reality